A Rapid Assessment of Microalgal Concentration Using Turbidity Measurement for Shellfish Hatchery Seed Production - Huiping Yang; Jayme C. Yee (EDIS)
The goal of this study was to develop a rapid assessment of microalgal concentration using a turbidity meter to serve commercial shellfish hatcheries for feeding shellfish larvae and broodstock. We used four commonly used algal species, Tetraselmis suecica, Isochrysis galbana, Chaetoceros calcitrans, and Chaetoceros gracilis, generating serial dilutions of each and measuring cell concentrations and turbidity of each sample. We identified linear correlations between cell concentration and turbidity and established standard equations between cell concentration and turbidity for each species. We sampled and quantified algae from a shellfish hatchery using these equations and compared hemocytometer counts. No differences were found (P ≥ 0.174), indicating the accuracy of the equations. We expect that this method can provide a quick, accurate, easy method for shellfish hatcheries to quantify algal concentration and avoid either over- or underfeeding larvae and broodstock.